Effect of Different Lots of Mueller-Hinton Agar on the Interpretation of the Gentamicin Susceptibility of Pseudomonas aeruginosa - Pollock, Helen M. (1978)
Population distributions and quality control data for strains of Pseudomonas aeruginosa tested for gentamicin susceptibility on six lots of Mueller-Hinton agar were analyzed. The lots of agar were used in three University of Washington hospitals from April 1975 through October 1977. The analyses indicated that the performance of members of the P. aeruginosa populations in each hospital closely followed the performance of the quality control strain, P. aeruginosa ATCC 27853, when tested on each lot of Mueller-Hinton medium. The variability of zone diameters with the P. aeruginosa populations and the quality control strain indicated that a fixed indeterminate range (13 to 16 mm) of gentamicin susceptibility was not applicable to these organisms as it was with the Enterobacteriaceae. Variability in gentamicin susceptibility results was demonstrated in both minimal inhibitory concentration and disk diffusion tests when eight selected P. aeruginosa strains and the quality control strain were tested on each lot of medium. This variation in susceptibility to gentamicin was not related to the total Ca(2+), Mg(2+), or Zn(2+) content of each lot of medium. The data demonstrated that a moving indeterminate range of gentamicin susceptibility, 3 to 6 mm below the mean zone diameter of the quality control strain, was a suitable criterion for strains tested on a single medium lot. These results illustrate the importance of defining stringent performance standards for media used in the susceptibility testing of P. aeruginosa with gentamicin and other aminoglycoside antibiotics.